Strategic and focused solutions to challenges faced by medical postgraduate students, in performing research at a South African University - Kisansa, M.E.; Lubinga, M.H. (South African Journal of Higher Education, 2020)
Background and objectives: Poor research output is a major issue at some South African Universities especially among medical postgraduate students. A number of students struggle to complete the research component, which is a requirement for registration with the Health Professions Council of South Africa (HPCSA). Aim: To evaluate and uncover factors hindering research performance at a South African university, with a plan to implementing strategic and focused remedial action. Methods: Post-graduate students in the School of Medicine were enrolled in a cross-sectional descriptive study. Using self-administered questionnaires, students were requested to provide information on barriers hindering research performance. Raw data from questionnaires was captured and analysed using STATA software. Results: A total 125 questionnaires were returned however some participants did not answer all the questions. The major reasons for non-performance were cited as; lack of prior research experience with only 14 per cent having had prior research exposure. Regarding association of research methodology (REME) course attendance with students starting research activities, 90 per cent of those that had attended the REME course, had started research activities at the time of this study. Research supervision was cited as inadequate by 48 per cent of respondents, while 61 per cent cited excessive workload as factor another factor hampering research course attendance and research participation. Most students indicated the need to have research taught and incorporated in the Masters curriculum, with time ring-fenced for research activities. Conclusion: Prior research exposure and attendance of a research course were important factors influencing students’ participation in research and should be encouraged. The institution should strive to improve supervisory and mentoring support as well as provide bio-statistics support. There is a need to ring-fence time specifically for research activities in order to counter the workload issue as a deterrent to research activities.